A comprehensive survey on feature selection in the various fields of machine learning - Dhal, Pradip; Azad, Chandrashekhar (Applied intelligence (Dordrecht, Netherlands), 2022)
In Machine Learning (ML), Feature Selection (FS) plays a crucial part in reducing data’s dimensionality and enhancing any proposed framework’s performance. However, in real-world applications, FS work suffers from high dimensionality, computational and storage complexity, noisy or ambiguous nature, high performance, etc. The area of FS is very vast and challenging in its nature. There are lots of work that have been reported on FS over the various area of applications. This paper has discussed FS’s framework and the multiple models of FS with detailed descriptions. We have also classified the various FS algorithms with respect to the data, i.e., structured or labeled data and unstructured data for the different applications of ML. We have also discussed what essential features are, the commonly used FS methods, the widely used datasets, and the widely used work done in the various ML fields for the FS task. Here we try to view the multiple comparison experimental results of FS work in different result discussions. This paper draws a descriptive survey on FS with the associated area of real-world problem domains. This paper’s main objective is to understand the main idea of FS work and identify the core idea of how FS will be applicable in various problem domains.